The Hope of Heavenly Healing of Disability, Part 1, Theological Issues - Gould, James B. (Journal of disability & religion, 2016)
This is Part 1 of a two-part article. The elimination view affirms that the disabled will be healed in heaven. Amos Yong's retention view, by contrast, suggests that people with disabilities will remain disabled in heaven. In this article, I build a positive case, based on the biblical argument for healing, for the elimination of disabilities in heaven; I then critique Yong's exegetical arguments based on Christ's stigmata and eschatological imagery for the retention view.